The Effectiveness of Missouri Mathematics Projects Learning Model on Mathematical Creative Thinking Ability and Mathematical Disposition in Students - Nailatus Sa'adah; Mulyaningrum Lestari (Noumerico: Journal of Technology in Mathematics Education, 2024)
The purpose of this study was to determine whether the ability to think creatively mathematically using the Missouri Mathematics Project (MMP) learning model is more effective than the ability to think creatively mathematically using the expository learning model (lectures) and to determine the ability of mathematical dispositions using the Missouri Mathematics Project (MMP) learning model. More effective than the ability of mathematical dispositions using expository learning models (lectures). This research is a type of Quasi-Experimental Design research with a quantitative approach. Data collection techniques use two types of instruments, namely tests and questionnaires. This study’s population was all class VIII SMP Walisongo Pecangaan Jepara students, totalling 65 students. This study’s hypothesis tests are the independent sample t-test and the Manova test